Membangun Kepekaan dan Empati Audiens Melalui Storytelling dalam Dakwah Lembaga Filantropi Dompet Dhuafa - Fadhilah, Ade Ludfi; Riady, Tedi Selamet; Gibran, Cholil (IDARI: Jurnal Manajemen Dakwah, 2025)
This study analyzes how the philanthropic organization Dompet Dhuafa cultivates audience sensitivity and empathy through its storytelling strategy in outreach, particularly in video content shared on social media. In the context of philanthropic outreach, storytelling serves as a communication approach that conveys not only informative but also emotional messages, effectively engaging the audience and fostering sustainable social participation. Employing a qualitative descriptive approach, data was collected through observations of video content, documentation of audience comments, and purposive interviews. The analysis utilizes persuasive communication theory and the concept of empathy in outreach communication to examine how narratives in videos influence audience perception and emotional responses. The findings indicate that storytelling featuring real-life beneficiary stories successfully evokes empathy and social awareness, as reflected in emotional comments, increased donation participation, and changes in religious behavior. The discussion underscores that storytelling is an effective outreach strategy for philanthropic organizations like Dompet Dhuafa, where touching and authentic narratives serve as both a communication tool and a means of outreach that reinforces Islamic values and fosters emotional connections between the organization and its audience.